Dampak Relatable Ustadz Hanan Attaki yang Menginspirasi Gen Z untuk Mendekatkan Diri dengan Islam - Sri Diana Putri; Firda Aulianti; Alvida Dzattadini; Elva Hanov Rais Satianingsih; Vyanara Aulyadisha; Edi Suresman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the impact of Ustadz Hanan Attaki's digital preaching on Generation Z in bringing them closer to Islamic teachings. Using a relatable approach and content relevant to daily life, Ustadz Hanan Attaki effectively engages young audiences through digital platforms such as Instagram, YouTube, and TikTok. His casual yet profound communication style, the use of language familiar to young people, and interactive preaching strategies are key factors in his success. The results reveal that Ustadz Hanan Attaki's emotional approach and relevant content are effective in enhancing religious awareness, strengthening spiritual values, and encouraging active participation in religious activities. This study provides insights into the importance of adaptive and relevant preaching strategies to effectively reach younger generations.